DELVING INTO THE DEPTHS OF HISTORY: A CODICOLOGICAL STUDY ON TWO MANUSCRIPTS OF ‘TANBIHUL MASYI AL-MANSUB ILA THORIQ AL-QUSYASYI’ BY SHEIKH ABDURRAUF AS-SINGKILI - Widyasari, Rintina; Putri, Firsya Aulia; Hidayatullah, Achmad Diny (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2023)
ABSTRACTNusantara manuscripts are one of the cultural assets in Indonesia that have high value in the history of Indonesian culture. Many of the cultural research experts and activists have researched and studied in depth the manuscripts of the archipelago. Most of the archipelago manuscripts that are hundreds of years old are in very poor physical condition. This research aims to describe the ins and outs and the physical condition of two manuscripts of copies of the book Tanbihul Masyi al-Mansub ila Thoriq al-Qusyasyi by Sheikh Abdurrauf bin Ali al-Fanshuri as-Singkili. This research uses a descriptive-qualitative method with a codicological approach based on primary reference sources, namely two manuscript copies of Tanbihul Masyi al-Mansub ila Thoriq al-Qusyasyi. The secondary data sources are articles, books, and literature related to codicology studies. Based on the results of research related to the ins and outs of manuscripts, it is revealed that the two manuscripts of the copy of Tanbihul Masyi between the Lengkong version of West Java and the Pustaka Kitab Jawi Lama Pantonlabu Aceh version have very different physical aspects. The Lengkong version of the manuscript, which is a ± 165 year old copy, is in poor physical condition, with many sheets and writings missing and illegible. The manuscript can only be seen digitally through the website. While the manuscript version of Pustaka Kitab Jawi Lama is in good physical condition and well preserved because it has been copied and reproduced for the public to enjoy.Keywords: Codicology, Manuscript Criticism, Sheikh Abdurrauf as-Singkili, Tanbihul al-Mansub Ila Thoriq al-Qusyasyi. ABSTRAKNaskah Nusantara merupakan salah satu aset budaya di Indonesia yang bernilai tinggi dalam sejarah kebudayaan Indonesia. Banyak dari para pakar peneliti budaya dan aktivis yang meneliti dan mengkaji secara mendalam naskah nusantara. Sebagian besar naskah nusantara yang berumur ratusan tahun kondisi fisik dan keadaannya sangatlah buruk. Penelitian ini bertujuan untuk mendeskripsikan seluk beluk dan kondisi fisik dari dua naskah salinan kitab Tanbihul Masyi al-Mansub ila Thoriq al-Qusyasyi karya Syekh Abdurrauf bin Ali al-Fanshuri as-Singkili. Penelitian ini menggunakan metode deskriptif-kualitatif dengan pendekatan kodikologi berdasarkan sumber acuan primer, yakni dua naskah salinan kitab Tanbihul Masyi al-Mansub ila Thoriq al-Qusyasyi. Adapun sumber data sekunder berupa artikel, buku, dan literatur yang berkaitan dengan kajian kodikologi. Berdasarkan hasil penelitian terkait seluk beluk pernaskahan terungkap bahwa dua naskah salinan kitab Tanbihul Masyi antara versi Lengkong Jawa Barat dan versi Pustaka Kitab Jawi Lama Pantonlabu Aceh mempunyai aspek fisik naskah yang sangat berbeda. Naskah versi Lengkong yang merupakan salinan berusia ±165 tahun kondisi fisiknya buruk, banyak lembaran dan tulisan yang hilang serta tidak terbaca. Naskahnya pun hanya dapat dilihat secara digital melalui laman website. Sedangkan naskah versi Pustaka Kitab Jawi Lama dalam kondisi fisik yang bagus dan terawat karena sudah di salin dan perbanyak untuk dinikmati masyarakat.Kata kunci: Kodikologi, Kritik Naskah, Syekh Abdurrauf as-Singkili, Tanbihul al-Mansub Ila Thoriq al-Qusyasyi